Tinjauan Trilogi Kerukunan Umat Beragama Berdasarkan Perspektif Iman Kristen - Yonatan Alex Arifianto; Joseph Christ Santo (Angelion, 2020)
Abstract: In Indonesia as a multicultural country, there is a diversity of beliefs. History proves that unhealthy exclusivism endangers pluralism. Differences in religious beliefs can become a potential for horizontal conflict if the state does not act to prevent this. In order to create a harmonious society, the government has launched the Religious Harmony Trilogy through the Regulation of the Minister of Religion and the Minister of Home Affairs. As citizens of Indonesia, Christians cannot neglect this harmony effort. This study aims to answer the problem of how the role of believers in social life in applying the Religious Harmony Trilogy based on the perspective of the Christian faith. This research uses descriptive analysis method through related literature. The results of this study indicate: first, Christianity teaches living in harmony among fellow Christians as members of the body of Christ. Second, Christianity teaches to be the light of the world and the salt of the world in the midst of people with different faiths, so that harmony can be created. Third, Christianity teaches submission to the government because the government is determined by God, thus creating harmony between Christians and the government.Abstrak: Di dalam negara Indonesia yang multikultural dijumpai adanya keberagaman keyakinan. Sejarah membuktikan bahwa eksklusivisme yang tidak sehat membahayakan kemajemukan. Perbedaan keyakinan agama bisa menjadi potensi konflik horizontal apabila negara tidak bertindak mencegah hal tersebut. Dalam rangka mewujudkan masyarakat yang harmonis, pemerintah telah mencanangkan Trilogi Kerukunan Umat Beragama melalui Peraturan Menteri Agama dan Menteri Dalam Negeri. Sebagai warga negara Indonesia, umat Kristen tidak bisa berlaku abai terhadap upaya kerukunan ini. Penelitian ini bertujuan untuk menjawab permasalahan bagaimanakah peran orang percaya dalam kehidupan bermasyarakat dalam mengaplikasikan Trilogi Kerukunan Umat Beragama berdasarkan persepektif iman Kristen. Penelitian ini menggunakan metode deskriptif analisis melalui literatur terkait. Hasil dari penelitian ini menunjukkan: pertama, kekristenan mengajarkan hidup rukun di antara sesama umat Kristen sebagai anggota tubuh Kristus. Kedua, kekritenan mengajarkan untuk menjadi terang dunia dan garam dunia di tengah-tengah masyarakat dengan keyakinan iman yang berbeda, sehingga tercipta keharmonisan. Ketiga, kekristenan mengajarkan penundukan kepada pemerintah karena pemerintah ditetapkan oleh Allah, dengan demikian terwujud kerukunan antara umat Kristen dengan pemerintah.